Effects of Parent Teacher Council Training Programme on School Environment at Primary Level in Khyber Pakhtunkhwa (Journal of Social Sciences Review, 2024)
Training is the modification of behavior in a formal manner. In fact, employees always need training for their professional development. The government of Khyber Pakhtunkhwa took a revolutionary step regarding the capacity building of the parent-teacher council (PTC) under a continuous capacity development program. A descriptive analysis method was performed to take a sample of 612 PTC members (Chairman and Secretaries). A questionnaire was designed to determine the effect of PTC on the school environment, and results were gathered in the context of the established objectives. The hypothesis under study was that PTC's training program is at the primary level, with the research aiming to improve PTC members' performance by enhancing their capabilities. Cronbach alpha test was used for the pilot study. The Validity and reliability of sampling data were measured. Training delivery is aimed at improving the school's learning environment through public-private participation. Analysis of the available data concluded that PTC's main work is financial management and the utilization of school funds. Teachers and parents are the drivers for the promotion of education. This training program of PTCs fosters educational development at the grassroots level through central and integral roles with a clear focus on school management and social accountability, improving gender-responsive education delivery.
Keywords: Parents Teacher Council (PTC); Education Management Information System (EMIS); Effect of Parent Teacher Council (EOPTC); Hurdle Faced By Parent Teacher Council (HFPTC); National Education Policy (NEP)